Women's writing of ancient Mesopotamia an anthology of the earliest female authors - Halton, Charles 1978-; Svärd, Saana 1977- (Cambridge University Press, 2018)
Women's Writing of Ancient Mesopotamia presents fresh and engaging translations of works that were composed or edited by female scribes and elite women of the ancient Near East. These texts provide insight into the social status, struggles, and achievements of women during the earliest periods of recorded human history (c.2300–540 BCE). In three introductory chapters and a concluding chapter, Charles Halton and Saana Svärd provide an overview of the civilization of ancient Mesopotamia and examine gender by analyzing these different kinds of texts. The translations cover a range of genres, including hymns, poems, prayers, letters, inscriptions, and oracles. Each text is accompanied by a short introduction that situates the composition within its ancient environment and explores what it reveals about the lives of women within the ancient world. This anthology will serve as an essential reference book for scholars and students of ancient history, gender studies, and world literature